Pengaruh Kualitas Produk, Daya Tarik dan Promosi Terhadap Loyalitas Pelanggan Harapan Jaya Dapur 12 Batam - Febriana Valentin Manalu; Nora Pitri Nainggolan (Komunitas Dosen Indonesia, 2023)
Today's retail business has proliferated in all places, which has resulted in intense competition that must be faced. customers by paying attention to product quality, attractiveness, and existing promotions. This research is a quantitative research with a population of buyers who make purchases at the Harapan Jaya Building Store, a sample of 204 samples with the results showing that Product Quality has a value of 4,141 greater than the value of t table of 1,972, attractiveness of Attractiveness of 3,009 greater than the t table value is 1,972, and the promotion is 5,196 greater than the t table value of 1,972 which concludes that the independent variables have a partial effect and the simultaneous test shows the results of 113,130 are greater than the F table value of 2.42 which concludes that the independent variables simultaneously influence the burden hopeful customers. The coefficient of determination test also shows that the size of the independent variable can explain the dependent variable by 62.4% with other factors of 37.6% and the rest is influenced by other variables